Antibacterial evaluation and phytochemical analysis of certain medicinal plants, Western Ghats, Coimbatore - Doss A; V, Parivuguna; M, Vijayasanthi; Surendran, Sruthi (Journal of Research in Biology, 2011)
The antibacterial effect of some selected Indian medicinal plants were evaluated on bacterial strains Staphylococcus aureus, Proteus mirabilis, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumonia and Salmonella typhi. The solvents used for the extraction of plants were petroleum ether, chloroform ethanol and methanol. The in-vitro antibacterial activity was performed by disc diffusion method. The most susceptible gram positive bacteria were S. aureus while the most susceptible gram negative bacteria were E.coli. The most active antibacterial plant was P.maximum. The significant antibacterial activity of active extracts were compared with the standard antimicrobials Ciprofloxacin (10mcg/ml). The results obtained in the present study suggest that P.maximum can be used in treating disease caused by the test organisms.